Montréal Expo 67 : L'Art moderne en Europe. - Martin, Kurt; Montreal Expo 1967 (Brussel : E.G.I., 1967)
Adam, Henri-Georges ; Afro ; Alechinsky, Pierre ; Antes, Horst ; Appel, Karel ; Baj, Enrico ; Baljeu, Joost ; Balthus ; Bazaine, Jean ; Bertrand, Gaston ; Bissier, Julius ; Bissière, Roger ; Burri, Alberto ; Burssens, Jan ; Cagli, Corrado ; Capogrossi, Giuseppe ; Constant ; Corneille ; Couzijn, Wessel ; Debré, Olivier ; Dorazio, Piero ; Dunoyer de Segonzac, André ; Fassbender, Joseph ; Fautrier, Jean ; Fontana, Lucio ; Ghysels, Jean-Pierre ; Gillen, François ; Guttuso, Renato ; Hartung, Hans ; Ipousteguy, Jean ; Klapheck, Konrad ; Landuyt, Octave ; Lapicque, Charles ; Van Lint, Louis ; Magnelli, Alberto ; Manessier, Alfred ; Mastroianni, Umberto ; Meier-Denninghoff, Brigitte ; Morlotti, Ennio ; Mortier, Antoine ; Nay, Ernst Wilhelm ; Nele, E. R. ; Oelze, Richard ; Perilli, Achille ; Pignon, Edouard ; Pomodoro, Gio ; Probst, Joseph ; Rotella, Mimmo ; Roulin, Félix ; Schultze, Bernard ; Schumacher, Emil ; Soulages, Pierre ; de Staël, Nicolas ; Tajiri, Shinkichi ; Trier, Hann ; Trökes, Heinz ; Vedova, Emilio ; Villon, Jacques ; Volten, André ; Wagemaker, Jaap ; Wercollier, Lucien ; Werner, Theodor ; Werthmann, Friedrich ; Westerik, Co ; Winter, Fritz ; Wols
biog. per kunstenaar
Frans & Engels
Montréal Expo 67, Pavilion of the European Community Montréal, 28.04 - 27.10.1967, European Community
boek
Keywords: Canada